Uruguay : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper describes economic developments in Uruguay during the 1990s. Real GDP expanded on average by more than 4 percent a year in 1990-94 and fell by 2 1\2 percent in 1995. The rapid growth of output during 1990-94 reflected buoyant external demand from Uruguay's main trading partners (Argentina and Brazil), as well as progress in strengthening the public finances, reducing wage indexation, opening the economy, and curtailing government intervention. Consumer price inflation fell steadily from almost 130 percent during 1990 to 35 percent during 1995.